2018
DOI: 10.3389/fped.2018.00190
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Effects of Human Milk Oligosaccharides

Abstract: Human milk oligosaccharides (HMOs) comprise a group of structurally complex, unconjugated glycans that are highly abundant in human milk. HMOs are minimally digested in the gastrointestinal tract and reach the colon intact, where they shape the microbiota. A small fraction of HMOs is absorbed, reaches the systemic circulation, and is excreted in urine. HMOs can bind to cell surface receptors expressed on epithelial cells and cells of the immune system and thus modulate neonatal immunity in the infant gut, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
196
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(209 citation statements)
references
References 168 publications
2
196
0
3
Order By: Relevance
“…The IgG-seronegative whey pool showed a high unspecific neutralizing capacity. This might be due to milk oligosaccharides, which were shown to be highly abundant in milk and inhibit different intestinal and respiratory viruses [43] and might, therefore, also be able to interfere with the neutralization test system. Alternatively, sIgA might also influence the neutralization test system, but detailed data on the role of HCMV-specific-sIgA in epithelial based NT-assays are not available according to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The IgG-seronegative whey pool showed a high unspecific neutralizing capacity. This might be due to milk oligosaccharides, which were shown to be highly abundant in milk and inhibit different intestinal and respiratory viruses [43] and might, therefore, also be able to interfere with the neutralization test system. Alternatively, sIgA might also influence the neutralization test system, but detailed data on the role of HCMV-specific-sIgA in epithelial based NT-assays are not available according to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Even though there are many studies related to human milk oligosaccharides (HMOs) and their influence in the infant health [25], still is limited the number of studies reporting beneficial metabolic effects of GOS in the adult population. The available evidence shows, for example, that the supplementation with a GOS to healthy elderly volunteers decreased systemic and fecal proinflammatory markers associated with increases in Bifidobacterium spp., Lactobacillus-Enterococcus spp., and the C. coccoideseE.…”
Section: Galacto-oligosaccharides (Gos)mentioning
confidence: 99%
“…51 These findings suggest that narrowing research to single components could result in conflicting and even misleading findings and suggests that HM studies should implement a more holistic approach given the links between development of the immune system and both the gut microbiome 52 and HM oligosaccharides (HMO). 53 We found a high degree of heterogeneity between studies, usually straightforward, the investigation of relationships with concentrations in mature HM is more problematic, given the variability in breastfeeding patterns and volumes of HM consumed during the lactation. 61 Our systematic review highlights pitfalls in HM research, with results not being data adjusted for known confounding factors in many studies up to date with only a few using multivariate statistical analysis (Table S2).…”
Section: Discussionmentioning
confidence: 95%
“…The authors reported interactions between the immune markers and showed that networks of HM regulatory and pro‐inflammatory cytokines including TGF‐β1, IL‐1β, IL‐6 and IL‐10 are associated with tolerance to cow's milk development . These findings suggest that narrowing research to single components could result in conflicting and even misleading findings and suggests that HM studies should implement a more holistic approach given the links between development of the immune system and both the gut microbiome and HM oligosaccharides (HMO) …”
Section: Discussionmentioning
confidence: 99%